Copy number variation contributes to cryptic genetic variation in outbreak lineages of Cryptococcus gattii from the North American Pacific Northwest. (December 2016) - Steenwyk, Jacob; Soghigian, John; Perfect, John; Gibbons, John
Abstract Background Copy number variants (CNVs) are a class of structural variants (SVs) and are defined as fragments of DNA that are present at variable copy number in comparison with a reference genome. Recent advances in bioinformatics methodologies and sequencing technologies have enabled the high-resolution quantification of genome-wide CNVs. In pathogenic fungi SVs have been shown to alter gene expression, influence host specificity, and drive fungicide resistance, but little attention has focused specifically on CNVs. Using publicly available sequencing data, we identified 90 isolates across 212Cryptococcus gattii genomes that belong to the VGII subgroups responsible for the recent deadly outbreaks in the North American Pacific Northwest. We generated CNV profiles for each sample to investigate the prevalence and function of CNV inC. gattii . Results We identified eight genetic clusters among publicly available Illumina whole genome sequence data from 212C. gattii isolates through population structure analysis. Three clusters represent the VGIIa, VGIIb, and VGIIc subgroups from the North American Pacific Northwest. CNV was bioinformatically predicted and affected ~300–400 Kilobases (Kb) of theC. gattii VGII subgroup genomes. Sixty-seven loci, encompassing 58 genes, showed highly divergent patterns of copy number variation between VGII subgroups. Analysis of PFam domains within divergent CN variable genes revealed enrichment of protein domains associated with transport, cell wall organization and external encapsulating structure. Conclusions CNVs may contribute to pathological and phenotypic differences observed between theC. gattii VGIIa, VGIIb, and VGIIc subpopulations. Genes overlapping with population differentiated CNVs were enriched for several virulence related functional terms. These results uncover novel candidate genes to examine the genetic and functional underpinnings ofC. gattii pathogenicity.